The effect of college students’ technology acceptance on e-commerce adoption - Suryawirawan, Okto Aditya (BISMA (Bisnis dan Manajemen), 2021)
This study aims to investigate e-commerce adoption using extended technology acceptance model (TAM) by adding self-efficacy and anxiety. The research samples included 233 undergraduate students were collected using an online survey form distributed through chat groups and social media. The collected data were analysed using partial least square-structural equation modelling (PLS-SEM) to investigate the proposed hypotheses in the model. This study found that self-efficacy has no impact towards perceived usefulness, self-efficacy has positive significant impact towards perceived ease of use, anxiety has no impact on both perceived usefulness and perceived ease of use, perceived usefulness has positive significant impact towards attitude, perceived ease of use has no impact towards attitude, perceived ease of use has positive significant impact on perceived usefulness, perceived usefulness has no impact towards e-commerce adoption, perceived ease of use has positive significant impact towards e-commerce adoption, and attitude has a positive significant impact towards e-commerce adoption. These findings further confirmed that TAM not only could be used to predict e-ticketing, e-learning, e-payment, and e-commerce purchase adoption but also e-commerce entrepreneurship. This study also further confirmed that the relationship between extended variable such as self-efficacy and anxiety with TAM variables might vary according to where the investigation was being held.